Investigating the influence of changing ice surfaces on gravity wave formation impacting glacier boundary layer flow with large-eddy simulations - B. Goger; B. Goger; I. Stiperski; M. Ouy; L. Nicholson (Weather and Climate Dynamics)
Mountain glaciers are located in highly complex terrain, and their local microclimate is influenced by mountain boundary layer processes and dynamically induced gravity waves. Previous observations from turbulence flux towers, as well as large-eddy simulations, over the Hintereisferner (HEF) glacier in the Austrian Alps have shown that down-glacier winds are often disturbed by cross-glacier flow from the north-west associated with gravity waves. In this work, we explore how changing the ice surface coverage upstream of HEF influences this gravity wave formation and intensity and the feedback that this has on boundary layer flow over HEF. In semi-idealized large-eddy simulations, we explore the impact of changing surface properties on HEF's microclimate by removing the upstream glaciers only (NO_UP) and removing all ice surfaces (NO_GL). Simulations suggest that removing the upstream glaciers (which causes a change in boundary layer stratification from stable to unstable) leads to a weaker gravity wave that breaks earlier than in the reference simulation, resulting in enhanced turbulent mixing over HEF. As a consequence, this leads to higher temperatures over the HEF tongue. Removing all glaciers results – as expected – in higher temperatures of up to 5 K over the missing ice surfaces, while the gravity wave pattern is similar to that in the NO_UP simulation, indicating that the upstream boundary layer exerts dominant control over downstream responses in such highly dynamic conditions. Furthermore, the results show that the upstream glaciers have a stabilizing effect on the boundary layer, impacting gravity wave formation, downslope windstorm intensity, and their feedback on the flow structure in valleys downstream. This case study shows that a single glacier tongue is not isolated from its environment under strong synoptic forcing and that surrounding glaciers and local topography have to be taken into account when studying atmosphere–cryosphere exchange processes.